KEBIJAKAN ALI IBN ABI THALIB DALAM IJTIHAD - Mhd. Rasidin; Doli Witro; Imaro Sidqi (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2020)
Abstract: Historically, one of the reasons for Islam’s growth and development in various parts of the world is the nature of Islam that is never static in a law. In the context of these changes, the elasticity and flexibility of Islamic law in responding to the problems of human life are increasingly demanded and expected to be able to accommodate them. One way is to do ijtihad to determine the law of every new problem that arises. Evidenced since the time of the Prophet s.a.w., the practice of ijtihad is always done by friends when they cannot ask directly to the Prophet s.a.w. One of the best-known friends did ijtihad after Rasulullah s.a.w. died is Ali ibn Abi Talib. Starting from this description, the writer wants to see Ali ibn Abi Talib’s policy of ijtihad. This paper uses qualitative research methods that are library research. The data in this paper is sourced from books, journals, articles discussing Ali ibn Abi Talib, and ijtihad. After the data is collected, it is then analyzed and analyzed with data analysis techniques, namely data reduction, data presentation, and conclusion drawing. The analysis shows that in the Ali ibn Abi Talib’s ijtihad has its patterns and methods in istinbath or establishing Islamic law (fiqh). His determination to hold on to the verses of the Al-Quran as a whole and his carefulness to judge a Sunah, as well as his flexibility in using the ra’yu (reason) was a distinctive feature for Ali ibn Abi Talib in dealing with the legal polemic that occurred in the society at that time.Keywords: Ali ibn Abi Thalib; Ijtihad; Policy